Job Stress, Depression and Work-to-Family Conflict: A Test of the Strain and Buffer Hypotheses - Wallace, Jean (Relations industrielles / Industrial Relations, 2005)
In this paper, the Job Demand-Control (JDC) model is used to predict depression and work-to-family conflict for married lawyers working full-time. The objectives of this paper are: (1) to determine whether the JDC model applies to work-to-family conflict; (2) to incorporate domain-specific job demand and job control variables; and (3) to examine a wider array of different forms of social support. First, the JDC model also helps explain work-to-family conflict. Second, domain-specificity does not appear key to documenting the buffering effects for job control. Third, spouse’s support of one’s career has the strongest main effect on both depression and work-to-family conflict, whereas coworker support functions as a moderator of lawyers’ job demands and has both buffering and amplifying effects. This paper closes by discussing the possible conditions under which members of support systems may transfer or exacerbate stress effects rather than alleviate them.